Who goes there? : an analysis of North Island brown kiwi (Apteryx mantelli) vocal anatomy, vocalisations, and associated behaviours : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Manawatū, New Zealand - Urquhart, Liam (Massey University, 2025)
This thesis explores individual variations in the vocal tract, vocalisations, and calling behaviour of the North Island brown kiwi (Apteryx mantelli). Kiwi are cryptic, nocturnal birds and are commonly monitored using acoustic methods – either manual call counts, or automated field recordings. Kiwi are loud callers with males and females producing very different calls. The number of times an individual bird calls per night varies, therefore turning call rates into estimates of population abundance is challenging and thus call counts fall short of estimating population numbers. This thesis aims to improve the knowledge we have of kiwi vocal behaviour using two approaches: (i) examining and describing for the first time the complete vocal tract of kiwi looking for differences between the sexes that could explain the different sounds they produce, and (ii) attempting to identify individuals through call variables obtained through multiple manual and automated call recordings. I also utilised calls shared between multiple recorders in an area to triangulate their location and identify a trend in call location selection. I investigated this to link calling behaviour to calling purpose, as the close proximity of kiwi nests on Ponui Island may influence calling for nest defence. Anatomical analysis of six brown kiwi (male = 3, female = 3) revealed a considerable difference in lateral labium area between the sexes (male = 2.43 mm2 ± 1.1, female = 1.19 mm2 ± 0.95), though this was not statistically significant (Mann-Whitney U test: n = 6; p = 0.3827), likely influenced by a small sample size. The syrinx was of the tracheobronchial type, which was larger in females (length = 8.98mm ± 2.78; width = 9.24mm ± 0.96), than in males (length = 6.13mm ± 0.8; width = 8.51mm ± 0.47). The tongue was spoon-like with a cartilaginous tip, and the oropharyngeal cavity contained two pairs of pharyngeal folds posterior to the glottis and choana. Call recordings, collected passively from 29 recorders near nine nests on Ponui Island and manually from six males, were analysed using k-means clustering to assess individual call distinctiveness. Results indicated that individual calls could not be reliably classified (percentage of correct identifications = 9%) using the selected call variables. Choice of calling location was examined using a three-tiered call quality ranking system. I evaluated call quality based on the number of harmonics visible in the call recording, which correlates with distance between calling bird and the recorder. Using a negative binomial GLM I found that altitude was not a predictive factor in site selection; however, high elevation sites functioned as good listening vantage points for the acoustic recorders, with higher ranked calls significantly correlated with increasing altitude. These findings highlight important considerations for future research. The differences in the sound generation source between the sexes highlights a potential source of the brown kiwi's sexually dimorphic calls, however, the degree of neuromuscular control of call production must be investigated. Additionally, utilising syllable (a distinct segment of harmonics in a bird’s call) variables for individual identification is paramount as they seem to be more informative than using call (the full vocalisation) variables alone, thus potentially providing more evidence for vocal individuality in kiwi. More time is needed for both studies to provide informative results to account for limitations in sample sizes and to account for seasonal variability of kiwi calls. Addressing these challenges could improve passive acoustic monitoring techniques for kiwi and other cryptic nocturnal species.
Keywords: 310901 Animal behaviour; 310907 Animal physiological ecology